Perceptual Environment and Development of Cat Visual System - Turkel, Joseph (My University, 1974)
Kittens were raised with early visual input restricted to horizontal, vertical, or oblique (45°) lines to determine the oculomotor consequences of such early restriction, and the limits of early neural plasticity. {i) All animals developed pendular nystagmus (frequency 3-5 Hz) which appeared to be related to active visual search, and was lowest in amplitude for animals exposed to oblique lines. (ii) Many cats developed convergent squint which was most severe for those exposed to horizontal lines. (iii) Abnormal binocular functioning of visual cortical units was found in all restricted animals. (iv) The stimulus orientation of maximum response corresponded to the experienced orientation for most units encountered in the animals exposed to vertical or horizontal lines. (v) In animals exposed to oblique lines all stimulus orientations appeared to be represented in the cortex; units responding maximally to the experienced orientation were not most often encountered. The results were discussed in terms of possible anatomical constraints on visual plasticity and a preliminary model of visual development was explored.
Keywords: perceptual environment; development; cat visuals; cat; visual system